Imperfect markets and the properties of macro-economic-environmental models as tools for policy evaluation - Bernd Meyer; Gerd Ahlert (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
Computable General Equilibrium Models and Macro-Econometric Models are deeply disaggregated macro-economic systems, which are used in economic environmental studies to explain the emissions of pollutions and the extraction of resources. CGE models are based on neoclassical theory depicting equilibrium of perfectly competitive markets, whereas the macro-econometric models – better characterized as neokeynesian – have been developed from a critical position vis-a-vis neoclassical theory stressing the importance of market imperfections. The paper at hand shows that this fundamental difference in approach to a large extent is responsible for differences in modelling results concerning the impact of policy instruments on the economy, social relations and the environment. Furthermore the outcome of concrete model applications is affected by differences in both the construction of the references and the concrete implementation of the policy instruments in the models.
Keywords: E12; E13; E17; E27; F62; Q01; Q56; 330; Integrated Assessment Modelling; CGE models; Macro-Econometric Models; Neoclassical Theory; Neokeynesian Theory